Modulation of RTK by sEcad: a putative mechanism for oncogenicity in oropharyngeal SCCs. (1st April 2014) - Teng, X; Ma, L; Kyrkanides, S; Raja, V; Trochesset, D; Brouxhon, SM
<x xml:space="preserve">Abstract</x> Objective Heightened levels of sEcad are found in the serum of patients with cancer and correlate with an unfavorable prognosis and later‐stages of disease. In this study, we explored whether sEcad is elevated in human OPSCC specimens and FaDu cells. Additionally, we investigated sEcad‐EGFR and sEcad‐IGF‐1R interactions and performed a functional analysis of sEcad in OPSCC cancers. Materials and Methods sEcad, EGFR, and IGF‐1R levels were examined in human OPSCC specimens and cells by immunoblotting. sEcad‐EGFR and sEcad‐IGF‐1R interactions were examined by immunoprecipitation and immunoblot assays. Levels of sEcad on EGFR and IGF‐1R pathway components were evaluated by IB. The effects of sEcad on OPSCC proliferation, migration, and invasion were assessed using standard cellular assays. Results Statistical analysis demonstrated that sEcad levels were significantly higher in OPSCC primary tumors and cells compared with normal controls. IP studies indicated that sEcad associated with EGFR and IGF‐1R, and addition of sEcad resulted in a statistically significant increase in downstream signaling. Finally, cell‐based assays demonstrated enhanced sEcad‐induced proliferation, migration, and invasion, which was blocked by EGFR and IGF‐1R inhibitors. Conclusions These findings suggest that sEcad may play an important role in OPSCC oncogenicity via its interaction and activation of EGFR and IGF‐1R.